Cardiomegaly Masquerading as a Pediatric Thymoma: A Case Report - Figlewicz, Matthew R (Cureus, 2020)
Thymoma is a very rare pediatric tumor, accounting for less than 1% of all childhood mediastinal tumors with scant literature, and only 23 pediatric cases were identified by a pediatric tumor surveillance registry between 1973 and 2008. In contrast to adult thymomas, pediatric thymomas have an aggressive tendency, though the majority is discovered as incidental findings. Patient presentations to the emergency department (ED) are often subtle and non-specific such as dyspnea, cough, and chest pain, requiring a broad differential on the part of the emergency clinician. Because of this presentation, diagnosis often occurs later in the disease process when compared with adults. Chest radiograph may demonstrate an enlarged thymic shadow or cardiomegaly, necessitating further cardiac workup, commonly routed through cardiology. Computed tomography and biopsy are required for definitive diagnosis, requiring a multidisciplinary approach to management. We present a case of a 16-year-old female complaining of progressive dyspnea and chest pain over the course of one to two months with radiographic cardiomegaly. She was found to have a Masaoka stage III World Health Organization (WHO) type B3 thymic endothelial neoplasm and underwent surgical resection.